The landscape of cognitive function in recovered COVID-19 patients - Zhou, Hetong; Lu, Shaojia; Chen, Jingkai; Wei, Ning; Wang, Dandan; Lyu, Hailong; Shi, Chuan; Hu, Shaohua (Journal of psychiatric research, 2020)
This study aims to evaluate the impacts of COVID-19 on cognitive functions in recovered patients and its relationship with inflammatory profiles. Twenty-nine patients recovered from COVID-19 as confirmed by negative nucleic tests for two consecutive times were recruited. A total of 29 age-, gender- and education-matched healthy controls were also recruited. The cognitive functions of all subjects were evaluated by the iPad-based online neuropsychological tests, including the Trail Making Test (TMT), Sign Coding Test (SCT), Continuous Performance Test (CPT), and Digital Span Test (DST). Blood samples from all patients were collected for examining inflammatory profiles, including interleukin-2 (IL-2), IL-4, IL-6, IL-10, tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), and C-reactive protein (CRP). The relationship between cognitive functions and inflammatory profiles were analyzed by Pearson correlation. In results, although no significant differences were found in TMT, SCT, and DST between the two groups, patients with COVID-19 scored lower in the correct number of the second and third parts of CPT, they also scored higher in the missing number of the third part of CPT (all P < 0.05). In patients with COVID-19, there was a trend of significant difference for lower reaction time in the first and second parts of CPT (P = 0.050, and 0.051, respectively), as well as the lower correct number of the second part of CPT (P = 0.050). Correlation analysis showed that the reaction time for the first and second parts of CPT was positively correlated with the CRP levels (r = 0.557 and 0.410, P < 0.05). In conclusion, our findings indicated that cognitive impairments exist even in patients recovered from COVID-19, and might be possibly linked to the underlying inflammatory processes.